Integrated Pharmacological Analysis on the Mechanism of Fuyou Formula in Treating Precocious Puberty - Guo, Chunyan; Sun, Ning; Hu, Kaili; Bai, Guoliang; Zhang, Meng; Wang, Qian; Ding, Qian; Liu, Jing; Wang, Xiaoling; Zhao, Libo (Frontiers in Pharmacology, 2021)
Fu-you formula (FY), a TCM formula composed of twelve herbs, as an in-hospital preparation, has been used treat to precocious puberty (PP) for decades. However, the lack of phytochemical characterization and mechanism of FY remains the main limitation for its spreading. In this study, we analyze the components and mechanisms of FY in PP, based on the integrated pharmacology. Investigated main constituents, targets, pathways of FY by using an integrative pharmacology, and recognized main constituents by HPLC-MS/MS. Then, observed the levels of Follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estrogen (E2) in danazol-induced PP in Sprague–Dawley (SD) rats. Lastly, retrospective study analyzed the clinical data of 575 patients who were diagnosed PP, treated by the FY, and followed-up in our hospital from 2014-2020. The result that total of 116 important candidate targets were selected based on pharmacological analysis. Selected the top 10 values key targets such as the estrogen receptor alpha (ESR1), insulin-like growth factor 1 (IGF1), and cAMP-response element binding protein (CREB), were localized and the related gene functions were determined. Gene functions were associated with biological regulation, a cellular process, or signaling pathway, such as the Estrogen signaling pathway, MAPK signaling pathway and PI3K-Akt signaling pathway. By recognizing the five compounds related to the ESR1、IGF1、 CREB and LEP, which are Quercetin, kaempferol, Luteolin, Apigenin and Emodin. The results showed that the FY could effectively reduce E2, LH, and FSH levels in Sprague-Dawley rats. Furthermore, the results of the retrospective analysis of medical records showed that the FY could remarkably reduce E2 levels in girls with PP.